Identifying the carrier - The effect and validity of demise- and identity of carrier clauses in bills of lading - a comparative study - Weinmann, Jens (Department of Commercial Law, 2014)
This dissertation sets out to elaborate on the question who the carrier is under different jurisdictions with its underlying principles and concepts. Special consideration will thereby be given to the effect and validity of demise and identity of carrier clauses in bills of lading, which may influence the question of whether a bill of lading is a shipowners or a charterers bill of lading. [...] It will be shown, that there is no uniform approach regarding this problem under international law and will comment on the necessity of bringing about changes in international maritime law.